The right to defend under the “Blue Cards” procedure - Soćko, Michał (Rodzina w systemie wsparcia i pomocy osobom z problemem alkoholowym, 2020)
The subject matter of this article is the analysis of the right to defense within the framework of the “Blue Cards” procedure, by a person suspected of using domestic violence. Firstly, the reasons for introducing this procedure into the Act on Counteracting Domestic Violence are described, with emphasis on the flaws of criminal law in the examined area. Secondly, an analysis of the definition of domestic violence and family member is performed. Thirdly, this article discusses the legal steps a person suspected of violence can take to prove his/her innocence of the allegation. This issue is very important since the initiation and conduct of the “Blue Cards” procedure and, even more so, the proof of domestic violence, can cause a number of negative consequences for the suspect, both legal and factual. This procedure may directly affect issues such as the ruling on whether and which spouse is at fault for the breakdown of marriage, and thus the right to maintenance, deprivation or limitation of parental rights, determination and manner of contacts with children or even the perception of a person in the professional environment or workplace.